2011
DOI: 10.1007/s10811-011-9772-2
|View full text |Cite
|
Sign up to set email alerts
|

Mixotrophic and photoautotrophic cultivation of 14 microalgae isolates from Saskatchewan, Canada: potential applications for wastewater remediation for biofuel production

Abstract: suitable for microalgal biofuel production due to unfavorable climate and solar insolation levels. However, these conditions can potentially be mitigated by coupling microalgal cultivation to industrial processes such as wastewater treatment. In this study, we have examined the biomass and lipid productivity characteristics of 14 microalgae isolates (Chlorophyta) from the Canadian province of Saskatchewan. Under both photoautotrophic and mixotrophic cultivation, a distinct linear trend was observed between bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 109 publications
(57 citation statements)
references
References 30 publications
2
48
0
1
Order By: Relevance
“…The isolates were identified by DNA sequence analysis of 18S, ITS1 and ITS2 regions (Eurofins Genomics, Huntsville, AL, USA) [19]. Species included Chlorella vulgaris, Nannochloris bacillaris, Tetracystis sp.…”
Section: Microalgae Cultivationmentioning
confidence: 99%
“…The isolates were identified by DNA sequence analysis of 18S, ITS1 and ITS2 regions (Eurofins Genomics, Huntsville, AL, USA) [19]. Species included Chlorella vulgaris, Nannochloris bacillaris, Tetracystis sp.…”
Section: Microalgae Cultivationmentioning
confidence: 99%
“…The six microalgae species used in this study were previously identified as promising candidates for carbon sequestration and biomass production in Northern climates (Bjornsson et al 2012;McGinn et al 2012;Park et al 2012;Bhatti et al 2014;Tibbetts et al 2014Tibbetts et al , 2015a. As such, they were mass cultivated in illuminated 1000-L enclosed photobioreactors to produce sufficient biomass for evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Microalgae and culture medium C. pyrenoidosa was collected from Department of Biotechnology, IIT Roorkee and grown in BG11 culture medium (without adding carbon source) (Park et al 2011;Yadavalli and Heggers 2013).The composition of BG11 media are given in Tables 1 and 2 as follows:…”
Section: Methodsmentioning
confidence: 99%